Las nociones básicas para desarrollar el área perceptiva cognitiva en los niños de primer año de Básica de la Unidad Educativa Intercultural Bilingüe “Jacobo Yépez” Parroquia Sicalpa, Cantón Colta, Provincia de Chimborazo. año lectivo 2014-2015 - Curichumbi Yumbillo, Maria Rosa (2016)
This research aim to analyze the impact of the basic notions in the development of cognitive perceptual area in children of first year of basic education at the Unidad Educativa Intercultural Bilingue "Jacobo Yépez". It is extremely important this study because the development of perceptual area is critical to stimulate the cognitive process in addition that mental skills are enriched and serve as a base for life, owns in the first year of basic education. To carry out the investigation it raises the following hypothesis: The application of basic notions affects the development cognitive perceptual area in children. The method used was the inductive-deductive. The research was exploratory, descriptive, bibliographical, documentary and transversal. The techniques used were observation and survey with their instruments and observation guide and questionnaire. The collected data were tabulated and presented in charts and graphs. In conclusion it is stated that: The basic notions area more developed are motor and affective also the less developed areas are the cognitive and the basic notions, which affects the development and construction of basic concepts and according to their possibilities since the initial learning of the basic notions are critical to stimulate the cognitive area. The level of Perceptive Cognitive area development in children is reached, the learning which has a progress learn to master motor skills and adapt their body movement, so that children develop and achieve goals. It was determined that the basic notions positive impact on the development of Cognitive Perceptual area, being a gradual process that builds the child from the experiences of children in the first year of basic education at the Unidad Educativa Intercultural Bilingue "Jacobo Yépez".